Recent Advances in the Development of Highly Conductive Structured Supports for the Intensification of Non-adiabatic Gas-Solid Catalytic Processes: The Methane Steam Reforming Case Study - Balzarotti, Riccardo; Ambrosetti, Matteo; Beretta, Alessandra; Groppi, Gianpiero; Tronconi, Enrico (Frontiers in Chemical Engineering, 2022)
Structured catalysts are strong candidates for the intensification of non-adiabatic catalytic processes thanks to their superior heat and mass transfer properties combined with low pressure drops. In the past two decades, different types of substrates have been proposed, including honeycomb monoliths, open-cell foams and, more recently, periodic open cellular structures produced by additive manufacturing methods. Among others, thermally conductive metallic cellular substrates have been extensively tested in heat-transfer limited exo- or endo-thermic processes in tubular reactors, demonstrating significant potential for process intensification. The catalytic activation of these geometries is critical: on one hand, these structures can be washcoated with a thin layer of catalytic active phase, but the resulting catalyst inventory is limited. More recently, an alternative approach has been proposed, which relies on packing the cavities of the metallic matrix with catalyst pellets. In this paper, an up-to-date overview of the aforementioned topics will be provided. After a brief introduction concerning the concept of structured catalysts based on highly conductive supports, specific attention will be devoted to the most recent advances in their manufacturing and in their catalytic activation. Finally, the application to the methane steam reforming process will be presented as a relevant case study of process intensification. The results from a comparison of three different reactor layouts (i.e. conventional packed bed, washcoated copper foams and packed copper foams) will highlight the benefits for the overall reformer performance resulting from the adoption of highly conductive structured internals.